Analisis Penyebaran dan Radius Jangkauan Fasilitas Kesehatan di Kabupaten Way Kanan Berbasis Sistem Informasi Geografis - Ewaldo, Kevin; Naulibasa, Gitta Vania (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
Geospatial Information System (GIS) is a system that can be used to assist in making decisions based on the spatial analysis performed. GIS can be used in various disciplines according to its purpose. One of the functions of GIS is to determine the distribution and radius of coverage of public facilities in an area. An increase in the population in an area will affect the use and need for available public facilities. One type of public facility that is urgently needed is a health facility. Way Kanan Regency is one of the areas experiencing an increase in population. Increasing the population in an area must be supported by the construction of adequate and equitable health facilities in each region. Based on this description, a geographic information system-based analysis is needed to determine the distribution of health facilities and their radius of coverage to the pattern of population settlements in Way Kanan Regency. The method used in this research is spatial analysis with the buffer method. Based on the results of the analysis, it was found that the distribution of health facilities in Way Kanan Regency was not evenly distributed and there were several sub-districts that had not been reached by health facilities. This is evidenced by several sub-districts in Way Kanan Regency which are outside the radius of the service coverage of health facilities. The suggestion in this study is to increase the number of health facilities, taking into account the existing settlement patterns.